Ipazia: reinterpretazioni teatrali e romanzesche francesi del ventesimo secolo (Itinera, 2012)
The fictions about Ipazia aim to answer the questions that history left unanswered. The authors create their own Ipazia according to the rules of the literature genre they choose, or to the characteristics they want to highlight. They often adopt anachronistic interpretations to develop a dialogue between past and present.